THE INFLUENCE OF CELEBRITY ENDORSEMENT, BRAND IMAGE, AND SERVICE QUALITY ON PURCHASING DECISIONS AT GURLBUCKET STORE - Sundari Dewi; Gede Bayu Rahanatha (Adisam Publisher, 2025)
The development of the fashion industry in Indonesia, especially women's fashion, tends to be caused by changes in fashion trends which have led to the emergence of the ready-to-wear concept, namely fast fashion. With this potential, extensive business opportunities are created in the women's fashion sector. This research was conducted at the Gurlbucket Shop located on Jl. Raya Padang Luwih No. 193, Dalung, North Kuta, Badung. The purpose of this research is to test and explain the influence of celebrity endorsement, brand image, and service quality on product purchasing decisions at the Gurlbucket Store. The sample in this study was 126 respondents. Data collection was carried out by distributing questionnaires directly delivered to the location and given directly to respondents. The collected data was analyzed using the classic assumption test, multiple linear regression analysis, determination test (Adjusted R2) and model feasibility test (F-test). The results of this research show that celebrity endorsement has a positive and significant influence on purchasing decisions, brand image has a positive and significant influence on purchasing decisions and service quality has a positive and significant influence on purchasing decisions at the Gurlbucket Store. The implications of this research can be material for consideration and input for the Gurlbucket Store in maintaining purchasing decisions by considering the variables celebrity endorsement, brand image and service quality.